Successful Interference with Cellular Immune Responses to Immunogenic Proteins Encoded by Recombinant Viral Vectors - Adélaïda Sarukhan; Sabine Camugli; Bernard Gjata; Harald von Boehmer; Olivier Danos; Karin Jooss (2001)
ABSTRACT Vectors derived from the adeno-associated virus (AAV) have been successfully used for the long-term expression of therapeutic genes in animal models and patients. One of the major advantages of these vectors is the absence of deleterious immune responses following gene transfer. However, AAV vectors, when used in vaccination studies, can result in efficient humoral and cellular responses against the transgene product. It is therefore important to understand the factors which influence the establishment of these immune responses in order to design safe and efficient procedures for AAV-based gene therapies. We have compared T-cell activation against a strongly immunogenic protein, the influenza virus hemagglutinin (HA), which is synthesized in skeletal muscle following gene transfer with an adenovirus (Ad) or an AAV vector. In both cases, cellular immune responses resulted in the elimination of transduced muscle fibers within 4 weeks. However, the kinetics of CD4 + T-cell activation were markedly delayed when AAV vectors were used. Upon recombinant Ad (rAd) gene transfer, T cells were activated both by direct transduction of dendritic cells and by cross-presentation of the transgene product, while upon rAAV gene transfer T cells were only activated by the latter mechanism. These results suggested that activation of the immune system by the transgene product following rAAV-mediated gene transfer might be easier to control than that following rAd-mediated gene transfer. Therefore, we tested protocols aimed at interfering with either antigen presentation by blocking the CD40/CD40L pathway or with the T-cell response by inducing transgene-specific tolerance. Long-term expression of the AAV-HA was achieved in both cases, whereas immune responses against Ad-HA could not be prevented. These data clearly underline the importance of understanding the mechanisms by which vector-encoded proteins are recognized by the immune system in order to specifically interfere with them and to achieve safe and stable gene transfer in clinical trials.